INTEGRATED DEVELOPMENT OF QUALITY AND INFORMATION MANAGEMENT SYSTEMS IN ORGANIZED VEHICLE FLEET – POSSIBILITIES AND OPPORTUNITIES - Vasic, Milos; Brzakovic, Miodrag; Stanojevic, Nada (Journal of Applied Engineering Science, 2022)
The subject of this paper is a complementary area consisting of management systems (QMS) and information systems (IS), i.e., the theoretical and practical need for their parallel design, development, implementation and operation. Companies are increasingly concerned with managing the quality of their products and services in accordance with international standards. Designing a quality management system requires the intensive participation of managers and employees who perform analysis and reengineering of business processes and accompanying procedures. Very similar requisites and tasks characterize the design of a company's information system, but these two endeavours are most often implemented as separate projects, handled by different teams, equipped with unrelated methodologies. Within the scope of this paper, the author's ambition was to establish a model of synergistic connection of the information system and the quality management system through the establishment of a Quality management system suitability function and check to what extent the definition of common databases, integrated data model and information model confirms or refutes the hypothesis that the integration of QMS and IS contributes to better overall business results and individually improves each of the connected systems.
Keywords: Quality management system; Information system; Synergy; Vehicle fleet